Meningkatkan Hasil Belajar Peserta Didik Kelas VII pada Materi Kemampuan dan Keterbatasanku Melalui PBL di SMP Negeri 02 Ketungau Hilir Tahun Ajaran 2024/2025 - Maria Mahdalena (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
The provision of high-quality education is significantly influenced by key factors, specifically educators and students. Competent educators are likely to cultivate quality individuals, adhering to the philosophy that